Effect of spatial variability of soft clays on geotechnical design of braced excavations: A case study of Formosa excavation. (November 2018) - Luo, Zhe; Hu, Biao; Wang, Youwen; Di, Honggui
Abstract: This case study presents the effect of spatial variability of soft clays on the geotechnical serviceability assessment of braced excavations. Finite element modeling is performed to predict the excavation-induced wall and ground movement. The spatial variations in two key soil parameters are modeled as two correlated lognormal random fields. The system reliability-based serviceability assessment conducted in this case study shows that the system probability of serviceability failure is greater than or equal to that for each single failure mode, indicating that serviceability assessment considering an individual failure mode can result in unsafe predictions.